Bias in 238U decay chain members measured by γ-ray spectrometry due to 222Rn leakage. (February 2020) - Poręba, Grzegorz; Tudyka, Konrad; Walencik-Łata, Agata; Kolarczyk, Aleksander
Abstract: In this work we investigate and quantify how effectively the noble gas 222 Rn is trapped inside measurement beakers used in high-resolution gamma-ray spectrometry. We test six types of different beakers commonly utilized in γ spectrometry, including one novel construction, the γBeaker. We assessed 222 Rn leakage by injecting 222 Rn rich air into the examined beakers and investigated the abnormal decrease in 222 Rn daughters – 214 Pb and 214 Bi. The measured decay times were used to estimate the 222 Rn leakage. In addition, we investigated the influence of an additional beaker sealed with tape. However, the additional beaker sealing only slightly reduced the 222 Rn escape and was not reproducible. Almost every tested beaker exhibited heavy 222 Rn leakage. This may lead to an underestimation and radioactivity over-dispersion of 238 U decay chain members when they are measured via their 222 Rn daughter products. Highlights: We quantify how effectively noble gas 222 Rn is trapped inside HPGe measurement beakers. We test six different beakers used in HPGe γ spectrometry. Up to 99% of 222 Rn leakage. New 222 Rn tight beaker is proposed.